Bordetella pertussis infection in children with severe pneumonia, Philippines, 2012–2015. Issue 7 (15th February 2017) - ,; Saito, Mayuko; Frederick Quicho, Reynaldo; Perez, Mauricio; Joy Almonia, Daryl; De Leon-Asi, Lea; Tamaki, Raita; Sombrero, Lydia; Lupisan, Socorro; Oshitani, Hitoshi; Sadiasa, Alexander; Saito-Obata, Mariko; et al.
Highlights: Our study highlights the importance of pertussis in children with severe pneumonia in the Philippines. Most of the pertussis-positive mortality cases occurred in those less than 3 months of age. More attention should be given to the provision of the current EPI vaccines. Abstract: A case-comparison study was conducted based on an observational study of severe pneumonia among hospitalized children in the Philippines. The children, from 8 days to 13 years old and hospitalized with clinical diagnosis of severe or very severe pneumonia from August 2012 to February 2015, were recruited. Nasopharyngeal swabs were collected from 1152 cases and B. pertussis were detected from 34 cases by PCR. Pertussis-positive cases were more likely to have no fever, more than one week of coughing and breathing difficulty, decreased breathing sounds, and central cyanosis than pertussis- negative cases. The percentage of underweight was significantly higher in pertussis-positive cases than pertussis-negative cases. Pertussis-positive cases showed remarkably higher fatality rate than pertussis-negative cases. All of the fatal cases among pertussis-positive cases were less than 6 months old. More attention should be given to protect young infants from pertussis.